2013
DOI: 10.1055/s-0032-1328656
|View full text |Cite
|
Sign up to set email alerts
|

Application of Plant Metabonomics in Quality Assessment for Large-Scale Production of Traditional Chinese Medicine

Abstract: !The curative effects of traditional Chinese medicines are principally based on the synergic effect of their multi-targeting, multi-ingredient preparations, in contrast to modern pharmacology and drug development that often focus on a single chemical entity. Therefore, the method employing a few markers or pharmacologically active constituents to assess the quality and authenticity of the complex preparations has a number of severe challenges. Metabonomics can provide an effective platform for complex sample a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 100 publications
(102 reference statements)
0
25
0
Order By: Relevance
“…Metabolomics, as one of the post-genome era members, is the branch of science concerned with the quantitative understanding of the metabolite components of integrated living systems (organisms, tissues or cells) and their dynamic responses to changes in both endogenous and exogenous factors. Plant metabolomics can yield a large amount of qualitative and quantitative data on metabolites according to the organism-specific metabolic pathways, metabolic networks, and functions that the metabolites participate in; thus, biologically meaningful data can be retrieved [13]. Plant metabolomic studies have been of value for the identification of metabolites, regional differences, natural variations, and intraspecific and interspecific differences in citrus fruits [14,15], figs [16], and tomatoes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics, as one of the post-genome era members, is the branch of science concerned with the quantitative understanding of the metabolite components of integrated living systems (organisms, tissues or cells) and their dynamic responses to changes in both endogenous and exogenous factors. Plant metabolomics can yield a large amount of qualitative and quantitative data on metabolites according to the organism-specific metabolic pathways, metabolic networks, and functions that the metabolites participate in; thus, biologically meaningful data can be retrieved [13]. Plant metabolomic studies have been of value for the identification of metabolites, regional differences, natural variations, and intraspecific and interspecific differences in citrus fruits [14,15], figs [16], and tomatoes [17].…”
Section: Introductionmentioning
confidence: 99%
“…The first (most recent) 10 papers deal with type II diabetes or diabetic nephropathy, comparison between Europe and China on the safety of materials, the European Union (EU) herbals directive, plant metabolomics in quality assessment, various activities of selected herbs, and integrative nanomedicine. [12345678910] Examples of typical articles published in a Western medical journal are either original papers on interaction potential,[1112] or systemic and general reviews on the use of herbal medicines in various conditions,[1314] on the quality, efficacy, and safety,[15] on herb–drug interactions[1617] or herbal side effects, especially in hepatotoxicity. [18] A recurring theme in conclusions of these reviews was the lack of adequate scientific data to judge efficacy and/or safety and the less-than-desirable quality of the published data.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it was suggested that some traditional Chinese medicine (TCM) and their products demonstrated protective effect against ischemic injury [ 7 ]. Thus, justifying TCM use in ischemic stroke patients is principally based on the synergic effect of their multi-categories [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%